2014
DOI: 10.1186/1756-0500-7-606
|View full text |Cite
|
Sign up to set email alerts
|

Potential of cell-free supernatants from cultures of selected lactic acid bacteria and yeast obtained from local fermented foods as inhibitors of Listeria monocytogenes, Salmonella spp. and Staphylococcus aureus

Abstract: BackgroundFood-borne infections cause huge economic and human life losses worldwide. The most common contaminants of foods include Listeria monocytogenes Salmonellae and Staphylococcus aureus. L. monocytogenes is most notorious due to its tolerance to common food preservation methods and the risks it poses, including higher fatality rates. Safer, more efficacious control methods are thus needed. Along with food-borne pathogens, lactic acid bacteria (LAB) can also be found in foods. Some LAB isolates inhibit pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 30 publications
0
38
1
1
Order By: Relevance
“…Other researchers have also demonstrated that LAB strains are strongly active against indicator species (Fraga Cotelo et al ., ; Mariam et al ., ; Patel & Parikh, ). However, most researches (Sip et al ., ; Choesri et al ., ; Cizeikiene et al ., ; Wang et al ., ) demonstrated strong antilisterial activity of LAB isolates from foods, which was not observed in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers have also demonstrated that LAB strains are strongly active against indicator species (Fraga Cotelo et al ., ; Mariam et al ., ; Patel & Parikh, ). However, most researches (Sip et al ., ; Choesri et al ., ; Cizeikiene et al ., ; Wang et al ., ) demonstrated strong antilisterial activity of LAB isolates from foods, which was not observed in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, there are approximately 1.6 million cases of foodborne illnesses occurring related to 30 specified pathogens each year in Canada (Thomas, et al, 2013). Among the most widespread foodborne pathogenic organisms, Staphylococcus aureus is an important foodborne pathogen causing foodborne illnesses (Mariam et al, 2014;Wang, et al, 2013;Wang, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The exploitation of the inhibitory activity of the lactic bacteria appeared in recent years as an alternative treatment and even prevention of some foodborne toxiinfection (Mezaini et al, 2009;Obi et al, 2015;Khalid, 2011). Indeed the lactic acid bacteria are known to be non-pathogenic and Generally Regarded as Safe, and are increasingly used because of their probiotic properties (Zacharof and Lovitt, 2012;Mariam et al, 2014).…”
Section: Introductionmentioning
confidence: 99%